2015
DOI: 10.1021/acs.analchem.5b02949
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposite Based on Reduced Graphene Oxide Film Modified with Phenothiazone and Flavin Adenine Dinucleotide-Dependent Glucose Dehydrogenase for Glucose Sensing and Biofuel Cell Applications

Abstract: A novel composite material for the encapsulation of redox enzymes was prepared. Reduced graphene oxide film with adsorbed phenothiazone was used as a highly efficient composite for electron transfer between flavin adenine dinucleotide (FAD)-dependent glucose dehydrogenase and electrodes. Measured redox potential for glucose oxidation was lower than 0 V vs Ag/AgCl electrode. The fabricated biosensor showed high sensitivity of 42 mA M(-1) cm(-2), a linear range of glucose detection of 0.5-12 mM, and good reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 44 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…Oxygen-insensitive flavin adenine dinucleotide-dependent glucose dehydrogenase (FAD-GDH) has been given much attention recently and there has been an increasing numbers of related reports on biosensors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and biofuel cells. 13,14,[16][17][18] Recently, the structure of FAD-GDH from Aspergillus flavus was unveiled and it was found that an FAD cofactor is buried deeply (∼1.4 nm) below the protein surface. 19 Therefore, the main issue with FAD-GDH is the construction of an electron transfer configuration as in the case of FAD-glucose oxidase (GOD).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen-insensitive flavin adenine dinucleotide-dependent glucose dehydrogenase (FAD-GDH) has been given much attention recently and there has been an increasing numbers of related reports on biosensors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and biofuel cells. 13,14,[16][17][18] Recently, the structure of FAD-GDH from Aspergillus flavus was unveiled and it was found that an FAD cofactor is buried deeply (∼1.4 nm) below the protein surface. 19 Therefore, the main issue with FAD-GDH is the construction of an electron transfer configuration as in the case of FAD-glucose oxidase (GOD).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of electrode surfaces with graphene species can significantly increase the surface area due to introducing nano‐sized roughness. Also, the electrochemical processes can be facilitated due to unique electronic features of graphene species . Recently developed electrochemical procedure to peel off graphene flakes in situ from carbon fibers resulted in electrode materials with unique electrochemical properties, characterized by large surface area and increased electrochemical reversibility of electrochemical process (meaning increased interfacial electron transfer rate constants) ,,.…”
Section: Resultsmentioning
confidence: 99%
“…The use of micro‐ or nano‐structured carbon materials resulted in 3D‐electrodes with an increased total area and facilitated electron transfer processes. The most recent advances in the design of biofuel cells have been achieved with the use of graphene‐containing materials as the electrode support . These graphene‐containing materials have been actively studied for various bioelectrochemical applications, including lactate biosensing ,,.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced graphene oxide (RGO) is a highly conductive material and is especially suitable for enzyme-based biosensors because of its biocompatibility [47]. RGO has been used as a conductive platform with large surface area for nanometal stabilization [48].…”
Section: The Functions Of Mnps In Various Biosensor Typesmentioning
confidence: 99%